ANALISIS JUMLAH OBAT TERHADAP POTENTIALLY INAPPROPRIATE MEDICATIONS (PIMs) BERDASARKAN BEERS CRITERIA 2015 PADA PASIEN HIPERTENSI GERIATRI DI PUSKESMAS SIDOMULYO KOTA PEKANBARU - Septi Muharni reviewer; fina aryani (Jurnal Penelitian Farmasi Indonesia)
Potentially Inappropriate Medications (PIMs) is the use of drugs associated with the risk of side effects where there are safer alternative to treat the same condition. The number of drug is one of the factors that can cause errors in the prescription of drugs and may result in PIMs events. This study aims to look at the number of drugs, the incidence of PIMs, the number of PIMs events and PIMs categories as well as see the relation of the amount of drugs used against PIMs. This is an observational analytic descriptive research with cross sectional approach for 287 prescriptions of geriatric hypertension patients using the purposive sampling technique in Sidomulyo health center in Pekanbaru. Based on the number of drug, there were 60 patients who got the number of drug ≥5 and 226 patients who got the numbert of drug <5 . The incidence of identified PIMs was 77 patients, the highest number of PIMs received was 1 PIMs in 75 patients and found the one category which is the most accepted category by the patients. The correlation analysis of Contigency Coefficient showed that the number of drugs gives a moderate correlation and significant (r = 0.414; p = 0,000) to the incidence of PIMs and the number of PIMs events. It can be concluded that the number of drugs provides a significant correlation in the incidence of PIMs in geriatric patients.